Measuring fintech-driven financial inclusion for developing countries: Comprehensive Digital Financial Inclusion Index (CDFII) - Banik, Banna; Roy, Chandan Kumar (Economic Journal of Emerging Markets, 2023)
Purpose ― The main objective of this study is to develop a comprehensive digital financial inclusion index (CDFII) that accounts for technology-driven financial inclusion and to compare it with a traditional financial inclusion index (TFII) to enhance the measurement of fintech-driven financial inclusion across countries.Methods ― The study employs a three-stage principal component analysis (PCA) to construct the CDFII and TFII using the latest available data from 31 developing countries during the period 2015-2021. The CDFII incorporates a new sub-index measuring individual literacy levels for using financial services, along with existing sub-indices capturing the penetration, availability, and usage of DFS. By integrating digital financial inclusion (DFII) and TFII, the overall CDFII is estimated.Findings ― The findings reveal that the levels of DFII and CDFII are higher than TFII for most of the economies examined. This indicates the significant impact of technology-driven financial inclusion in expanding access to formal banking and non-banking financial services for previously unbanked populations.Implication ― The study implies that policymakers and researchers should prioritize the integration of technology-driven financial inclusion indicators, such as the comprehensive digital financial inclusion index (CDFII), into their assessments and interventions to ensure a more accurate and effective approach to promoting inclusive and sustainable economic development.Originality ― This study introduces the CDFII as a novel comprehensive index that addresses the shortcomings of traditional financial inclusion indices. By incorporating individual skill levels and considering dimensions specific to DFS, the CDFII provides a more accurate representation of fintech-driven financial inclusion levels. This contributes to the existing literature on financial inclusion measurement and provides a valuable analytical tool for researchers and policymakers.